ICU nurses' perception of visits to patients - Dobrinić, Ines (Array, 2020)
Introduction. Visits to patients are part of a positive and effective strategy of helping patients and their families to better adapt to the stress caused by a patient’s admission to an intensive care unit (ICU). Aim. To determine the ICU nurses’ perception of visits to patients. Methods. The study was conducted at the University Hospital Centre Zagreb (UHC). The cross-sectional study included nurses who work in ICUs. An anonymous, self-designed questionnaire was used and filled in by 44 respondents. The questionnaire consisted of 17 closed-ended questions pertaining to demographic data, questions related to information on visits and questions about the concept of open visits. Results. Out of the total number of 44 respondents, 25 respondents stated that their ICU has booklets about the manner of visits and visiting hours, and that they hand them out to families, while 19 respondents stated that they do not have such booklets. 61% of the respondents feel they have sufficient training to communicate with the patient’s family. 41% of the respondents said that the visits had a positive effect on the patient’s condition and only 2% stated that the visits had no positive effect. 57 % of the respondents think that visits sometimes have a positive effect on the patient’s condition. Of the total number of respondents, 84% feel that visiting hours should be limited. Respondents feel that visits sometimes impede them in their work (66%), while 59% of the respondents feel that visits help spread infections. Out of the total number of respondents, only 32% of them stated that they were familiar with the open ICU concept. Conclusion. More than half of the respondents stated that they have a written visiting policy on ICU wards, and that they are trained to communicate with the family members of patients. Most respondents feel that visits contribute to the spread of infections and that they would limit children’s visits to the ICU.